Designing polar textures with ultrafast neuromorphic features from atomistic simulations. Issue 1 (15th March 2023) - Prosandeev, Sergey; Prokhorenko, Sergei; Nahas, Yousra; Yang, Yali; Xu, Changsong; Grollier, Julie; Talbayev, Diyar; Dkhil, Brahim; Bellaiche, L
Abstract: This review summarizes recent works, all using a specific atomistic approach, that predict and explain the occurrence of key features for neuromorphic computing in three archetypical dipolar materials, when they are subject to THz excitations. The main ideas behind such atomistic approach are provided, and illustration of model relaxor ferroelectrics, antiferroelectrics, and normal ferroelectrics are given, highlighting the important potential of polar materials as candidates for neuromorphic computing. Some peculiar emphases are made in this Review, such as the connection between neuromorphic features and percolation theory, local minima in energy path, topological transitions and/or anharmonic oscillator model, depending on the material under investigation. By considering three different and main polar material families, this work provides a complete and innovative toolbox for designing polar-based neuromorphic systems.